Pengembangan Media Pembelajaran Assemblr Edu Berbasis Augmented Reality (AR) Mata pelajaran Matematika Materi Bangun Ruang Kelas V Sekolah Dasar - Fauzi, Nur Akhmad; Saputro, Hengkang Bara (Mandalika Mathematics and Educations Journal, 2025)
This study aims to develop Augmented Reality (AR)-based mathematics learning media using the Assemblr Edu application on the material of spatial figures for grade V elementary schools. The background of this study is based on the low motivation and understanding of students towards abstract material, as well as the limited use of technology in learning at Wirosaban Elementary School. The study used the Research and Development (R&D) method with a 4D development model modified into three stages: define, design, and develop. The results of the media validation showed very good quality with a score from media experts of 93.3%, material experts 80%, and learning experts 81.6%. The practicality test also showed very good results, namely 98.3% from teachers and 92.7% from students. This media is considered feasible and practical to be used as an alternative innovative learning to improve students' understanding and motivation to learn in understanding the concept of spatial figures. This study shows that the integration of AR technology in learning can provide a more interactive, interesting, and relevant learning experience to the needs of the 21st century.